2005
DOI: 10.1593/neo.04781
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tumor Tropism of Transplanted Human Neural Stem Cells Is Induced by Vascular Endothelial Growth Factor

Abstract: The transplantation of neural stem cells (NSCs) offers a new potential therapeutic approach as a cell-based delivery system for gene therapy in brain tumors. This is based on the unique capacity of NSCs to migrate throughout the brain and to target invading tumor cells. However, the signals controlling the targeted migration of transplanted NSCs are poorly defined. We analyzed the in vitro and in vivo effects of angiogenic growth factors and protein extracts from surgical specimens of brain tumor patients on N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(165 citation statements)
references
References 19 publications
8
155
0
2
Order By: Relevance
“…NSCs display remarkable tropism and migratory capacity to sites of malignant growth. 19,20 In this study, we chose the human F3 NSC cell line, as it is a well-characterized and a well-established human NSC line. 3,[5][6][7]11 No signs of local or systemic toxicity were observed in case of animals injected with F3 cells alone.…”
Section: F3cdifn-b Cells Increase the Survival Periods In Experimenmentioning
confidence: 99%
“…NSCs display remarkable tropism and migratory capacity to sites of malignant growth. 19,20 In this study, we chose the human F3 NSC cell line, as it is a well-characterized and a well-established human NSC line. 3,[5][6][7]11 No signs of local or systemic toxicity were observed in case of animals injected with F3 cells alone.…”
Section: F3cdifn-b Cells Increase the Survival Periods In Experimenmentioning
confidence: 99%
“…It is likely that tumorupregulated VEGF and angiogenic-activated microvasculature may be factors that mediate guidance signals for mesenchymal stem cells (MSC) tropism toward brain tumors. 74 There is evidence that active tumor sites attract exogenous MSCs rendering them attractive as delivery vehicles for various anticancer factors, including cytokines, pro-drugs and replicative adenovirus. 75 MSCs can be derived from bone marrow and they consist of multi-potent stem cells that are capable of differentiating into both mesenchymal and non-mesenchymal lineages.…”
Section: Stem Cellsmentioning
confidence: 99%
“…Besides, the genetic manipulations in ES cells or adult stem cells such as HSCs, endothelial progenitor cells (EPCs), mesenchymal stem cells (MSCs), and neural stem cells (NSCs) also present manifold potential to diminish the risk of rejection related with their in clinical applications. The genetically-altered stem cells could even be applied for reversing inherited genetic defects that are responsible for dissimilar pathological disorders (14,(35)(36)(37)(38). Gene therapies by using genetically altered stem cells as vehicles for the delivery of therapeutic agents at precise injured organ tissues also characterize promising approaches for treating various pathological disorders and cancers (7,14,23,(36)(37)(38)(39).…”
Section: Stem Cell Based-therapies In Regenerative Medicinementioning
confidence: 99%
“…The genetically-altered stem cells could even be applied for reversing inherited genetic defects that are responsible for dissimilar pathological disorders (14,(35)(36)(37)(38). Gene therapies by using genetically altered stem cells as vehicles for the delivery of therapeutic agents at precise injured organ tissues also characterize promising approaches for treating various pathological disorders and cancers (7,14,23,(36)(37)(38)(39). It has been demonstrated that genetically adapted migrating NSCs, which are capable to travel through the central nervous system and reach the extracranial neoplastic sites, may be transplanted in the animal models in vivo and specifically attracted to tumor sites due to the release of chemotactic signals such as vas- cular endothelial growth factor (VEGF) and stromal derived growth factor-1 (SDF-1) (36,37,39).…”
Section: Stem Cell Based-therapies In Regenerative Medicinementioning
confidence: 99%